Effective cybersecurity : understanding and using standards and best practices - Stallings, William 1945- (Upper Saddle River, NJ : Addison-Wesley, 2019)
"In Effective Cybersecurity, William Stallings introduces the technology, operational procedures, and management practices needed for successful cybersecurity. Stallings makes extensive use of standards and best practices documents that are often used to guide or mandate cybersecurity implementation. Going beyond these, he offers in-depth tutorials on the 'how' of implementation, integrated into a unified framework and realistic plan of action. Effective Cybersecurity aligns with the comprehensive Information Security Forum document 'The Standard of Good Practice for Information Security,' extending ISF's work with extensive insights from ISO, NIST, COBIT, other official standards and guidelines, and modern professional, academic, and industry literature. This knowledge is indispensable to every cybersecurity professional. Stallings presents it systematically and coherently, making it practical and actionable"--Back cover.
1. Guides to Practical Cybersecurity2. Security Governance3. Information Risk Assessment4. Security Management5. People Management6. Information Management7. Physical Asset Management8. System Development9. Business Applications Management10. System Access11. System Management12. Networks and Communications13. Supply Chain Management14. Technical Security Management15. Threat and Incident Management16. Local Environment Management Part Three: Security Monitoring and Improvement17. Business Continuity18. Security Monitoring and Improvement
Includes bibliographical references (pages 694-707) and index.
Keywords: Computer security; Computer security -- Standards; Information technology -- Management -- Security measures; Computer networks -- Security measures; Internet -- Security measures; COMPUTERS / Security / General; Computer networks -- Security measures; Computer security; Computer security -- Standards; Internet -- Security measures